2009
DOI: 10.1039/b901390c
|View full text |Cite
|
Sign up to set email alerts
|

Towards robust alkane oxidation catalysts: electronic variations in non-heme iron(ii) complexes and their effect in catalytic alkane oxidation

Abstract: A series of non-heme iron(II) bis(triflate) complexes containing linear and tripodal tetradentate ligands has been prepared. Electron withdrawing and electron donating substituents in the para position of the pyridine ligands as well the effect of pyrazine versus pyridine and sulphur or oxygen donors instead of nitrogen donors have been investigated. The electronic effects induced by these substituents influence the strength of the ligand field. UV-vis spectroscopy and magnetic susceptibility studies have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 76 publications
7
75
1
Order By: Relevance
“…62 These findings were supported by further topological variations of the BPMEN ligand system. [64][65][66] It was found that catalyst stability under oxidising conditions and can be altered by ligand tuning. Despite these efforts the best catalytic results in cyclohexane oxidation remained those achieved with the Please do not adjust margins Please do not adjust margins parent BPMEN ligand.…”
Section: Iron Nonheme Complexes Bearing Pure N-donor Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…62 These findings were supported by further topological variations of the BPMEN ligand system. [64][65][66] It was found that catalyst stability under oxidising conditions and can be altered by ligand tuning. Despite these efforts the best catalytic results in cyclohexane oxidation remained those achieved with the Please do not adjust margins Please do not adjust margins parent BPMEN ligand.…”
Section: Iron Nonheme Complexes Bearing Pure N-donor Ligandsmentioning
confidence: 99%
“…63 Substitution of the bridging nitrogen donors by oxygen or sulphur atoms (20a-d, Figure 11) results in a complete lack of catalytic activity. 65 In this context Britovsek et al 60,65 proposed that a strong ligand field inducing primarily low spin iron complexes positively influences catalytic activity and selectivity. A milestone was reached by Chen and White in 2007.…”
Section: Iron Nonheme Complexes Bearing Pure N-donor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…86-92% (Table S1, entries 31 and 34). Thus, the pronounced yield drops verified for cyclohexane oxidations when containing free radical scavengers corroborate the involvement of radical pathways that can compete with metal-based oxidations catalyzed by other Fe III complexes with N,O\ or O,O\ ligands [18,[32][33][34].…”
Section: Catalytic Activity Of Complexes 3 Andmentioning
confidence: 76%
“…Peroxidative oxidation of alkanes, in particular cyclohexane, is a widely used model to check and compare the activity of the complexes when biomimicking active sites of various oxygenases [32][33][34]. Moreover, alkane functionalization stands as a challenge for the establishment of hydrocarbon feedstocks, and new methodologies for C\H bond oxidation can result in synthetic strategies toward more complex and valuable organic products [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%